(untitled) (Research, Society and Development, 2020)
The article identifies the spatial concentration of production and analyzes the sources of growth and income instability of the corn crop in the state of Pará. Time series of harvested area, production, productivity, gross production value and corn prices in the state of Brazil were used. Pará, from 1990 to 2018, obtained from the Brazilian Institute of Geography and Statistics (IBGE). To assess the level of spatial concentration, the Locational Quotient and the Gini Index were determined. The assessment of the sources of growth was carried out based on the Shift-Share model, which allows decomposing the variation in the gross value of production in the effects of harvested area, yield and price. Income instability was estimated by determining the Cuddy Della Valle Index. The results indicate that fluctuations in the gross value of production in the early 1990s were associated with the expansion of cultivated areas, in contrast to the current scenario where fluctuations are greatly influenced by increased productivity. The most specialized microregions in corn production are: Paragominas, Conceição do Araguaia, Parauapebas and Santarém. The concentration of production is relatively high and the income generated by the crop shows low instability as it is strongly associated with price stability in recent years.